Upaya Peningkatan Keterampilan Membuat Poster dengan Topik Lingkungan Alam dan Sosial melalui Media Canva Siswa Kelas VI SD Negeri Bangsal 3 Kota Kediri - Ananta Dwi Kurniawan; Asry Oktafiani; Anisha Intan Wahyu Putri; Hanifa Rahma Yulisa; Shima Novia Widya Putri (Universitas Nusantara PGRI Kediri, 2024)
This study was motivated by the importance of improving poster-making skills on the theme of the natural and social environment among grade VI students of SD Negeri Bangsal 3, Kediri City, as well as the low motivation and variety of learning media used previously. This study aims to test the effectiveness of using the Canva application in improving these skills. Canva was chosen because of its ease of access, interactive features, and attractive visuals, which are relevant to technological developments and student interests. This study uses the Classroom Action Research (CAR) method with a descriptive analysis approach. The research participants were grade VI students of SD Negeri Bangsal 3, Kediri City, in the 2024/2025 academic year, totaling 28 students. The study was conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection stages. Data analysis was carried out descriptively quantitatively by comparing the average value of students' poster-making skills between cycles I and II. The results showed a significant increase in students' poster-making skills after using Canva. In cycle I, the lowest group score was 60 and the highest was 65. After the intervention in cycle II, the lowest score increased to 85 and the highest reached 90, with an average increase of 40.6%. This finding indicates that the use of Canva is effective in improving students' creativity and skills in designing digital posters with natural and social environmental themes.